THE SOUND AND THE FURY: TIME FRAGMENTATION - Tahmasebi, Leila (Journal of process management and new technologies, 2020)
This study is about individual and time in The Sound and the Fury. To what extend time rules an individual? When an individual is unable to overcome the power and dominance of time what destination awaits him? To answer this question, the present study explores the significance of time in The Sound and the Fury and how it affects the mentality of each character. To this end the real present which is created by the subconscious memories of the defeated characters, is set against the ideal present, the conscious promising present moment. Characters who are dominated by the power of the frustrating past events are unable to catch up with the social and personal transitions, thus the future fails for them. The obscure structure of the novel resulting from its unconventional time sequence is a projection of the characters’ involvement with time. In addition time can be considered as an element of modernism in modern work of art creating a sort of ambiguity which matches the complexity of modern era.